Leucine‐enriched whey protein supplementation, resistance‐based exercise, and cardiometabolic health in older adults: a randomized controlled trial. Issue 6 (14th September 2021) - Kirk, Ben; Mooney, Kate; Vogrin, Sara; Jackson, Matthew; Duque, Gustavo; Khaiyat, Omid; Amirabdollahian, Farzad
Abstract: Background: Increasing protein intake (above the Recommended Dietary Amount) alone or with resistance‐based exercise is suggested to improve cardiometabolic health; however, randomized controlled trials (RCTs) are needed to confirm this. Methods: The Liverpool Hope University‐Sarcopenia Aging Trial (LHU‐SAT) was a 16 week RCT (ClinicalTrials.gov Identifier: NCT02912130) of 100 community‐dwelling older adults [mean age: 68.73 ± 5.80 years, body mass index: 27.06 ± 5.18 kg/m 2 (52% women)] who were randomized to four independent groups [Control (C), Exercise (E), Exercise + Protein (EP), Protein (P)]. E and EP completed supervised and progressive resistance‐based exercise (resistance exercise: two times per week, functional circuit exercise: once per week), while EP and P were supplemented with a leucine‐enriched whey protein drink (three times per day) based on individual body weight (0.50 g/kg/meal, 1.50 g/kg/day). Outcome measures including arterial stiffness (pulse wave velocity), fasting plasma/serum biomarkers [glucose/glycated haemoglobin, total cholesterol, low‐density lipoprotein (LDL), high‐density lipoprotein, insulin, resistin, leptin, adiponectin, C‐reactive protein, tumour necrosis factor‐alpha, interleukin‐6, cystatin‐C, & ferritin], insulin resistance (HOMA‐IR), and kidney function (eGFR) were measured before and after intervention. Results: Total protein intake (habitual diet plus supplementation) increased to 1.55 ± 0.69 g/kg/day in EP and to 1.93 ± 0.72 g/kg/day in P, and remained significantly lower ( P < 0.001) in unsupplemented groups (E: 1.08 ± 0.33 g/kg/day, C: 1.00 ± 0.26 g/kg/day). At 16 weeks, there was a group‐by‐time interaction whereby absolute changes in LDL‐cholesterol were lower in EP [mean difference: −0.79 mmol/L, 95% confidence interval (CI): −1.29, −0.28, P = 0.002] and P (mean difference: −0.76 mmol/L, 95% CI: −1.26, −0.26, P = 0.003) vs. C. Serum insulin also showed group‐by‐time interactions at 16 weeks whereby fold changes were lower in EP (mean difference: −0.40, 95% CI: −0.65, −0.16, P = 0.001) and P (mean difference: −0.32, 95% CI: −0.56, −0.08, P = 0.009) vs. C, and fold changes in HOMA‐IR improved in EP (mean difference: −0.37, 95% CI: −0.64, −0.10, P = 0.007) and P (mean difference: −0.27, 95% CI: −0.53, −0.00, P = 0.048) vs. C. Serum resistin declined in P only (group‐by‐time interaction at 16 weeks: P = 0.009). No other interactions were observed in outcome measures ( P > 0.05), and kidney function (eGFR) remained unaltered. Conclusions: Sixteen weeks of leucine‐enriched whey protein supplementation alone and combined with resistance‐based exercise improved cardiometabolic health markers in older adults.